KONTRIBUSI KEPEMIMPINAN, KOMUNIKASI, TIM KERJA DAN ETIKA KERJA TERHADAP KUALITAS PEMBELAJARAN GURU SMK PEMBANGUNAN NASIONAL SUKOHARJO - WIJAYA , WAHYU (2011)
The aim in this research for: 1) Test of leadership, comunication, team work, and attitude of work have influence for teacher learning of quality at Vocational High School Pembangunan Nasional Sukoharjo; 2) Knowing where the factor between leadership, comu nication, team work, or attitude of work than be dominant can influence of teacher learning of quality at Vocational High School Pembangunan Nasional Sukoharjo. The method in this research is survey method with quantitative approach . The study took place in the National Development Vocational High School Sukoharjo. This study population is finite or the number of known for sure that teaching staff (teachers) vocational school in Sukoharjo district , with teachers as many as 71 people. But in this study, th e researcher uses all of the population as a sample , in order to obtain the results of research that is completely valid. The samples taken by the method of purposive sampling. The results of this study were: 1) hypothesis which states that the leadership, communication, teamwork, and work ethics affect the quality of vocational school teachers learning at Vocational High School Pembangunan Nasional Sukoharjo, proven. It is shown the results of F test of 14.957 is being observed was a partial one among the independent variables ie work ethic showed no significant effect on the quality of teacher learning. It is known from the results of t test Leadership variables obtained t count for = 2 .059 and ttable at n 71 and a 1% is 1 .667; ttable at n 71 and a 5% is 1 .994, so t count> ttable then Ho is rejected, it means that there is significant influence between the variables of leadership on the quality of this learning This reinforced the value of Sig 0.0 43 <0.05; communication variables obtained tcount = 4 .080 and 1.667 then tcount ttable => t table, so that Ho is rejected, it means that there is significant influence between the communication variables to the quality of this study reinforced the value of significance 0.000 <0.05 ; variables obtained t count for team work and ttable = 2.881 = 1 .667 then tcount> ttable, so that Ho is rejected, it means that there is significant influence between the variables of work teams on the quality of this study reinforced the value of significance 0.005 <0.05; and work ethic variables obtained t count for = 1 .003 and 1 .667 then tcount ttable => ttable, so that Ho is rejected, meaning there is no significant influence between the variables of work ethic on the quality of learning it reinforced the value o f significance 0.272 > 0.05; 2) The factors are more influential in between leadership, communication, team work, or work ethic on the quality of vocational school teachers learning at Vocational High School Pembangunan Nasional Sukoharjo is communication. It is shown from the largest score value on the regression coefficient of 0.7 60.